TINJAUAN HUKUM ISLAM TERHADAP TALANGAN DANA UMRAH PADA UJAS TOUR & TRAVEL - MELIANA OKI SYAH PUTRI; Hadi Daeng Mapuna (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2023)
Abstract Muamalah is an activity in which there are transactions between humans and humans, as well as between humans and their environment. This is what is often referred to as social life, where a person's status or position as a place or position in a social group, against other groups in a larger group. Humans were created by Allah swt. as social beings who always interact with other humans. Muslims are the majority of Indonesia's population, most Muslims certainly want to visit the holy land to carry out the pilgrimage and umrah in order to perfect the fifth pillar of Islam. Performing Umrah requires a lot of money, and not all Muslims can do it. Nowadays, Umrah is easier to do by utilizing the services and services of an Umrah travel agency, one of which is by using the Umrah bailout system. Based on this, it encourages the author to raise "Review of Islamic Law on Umrah Fund bailouts for Ujas Tour & Travel" as the title of this research. Muamalah is an activity in which there are transactions between humans and humans, as well as between humans and their environment. This is what is often referred to as social life, where a person's status or position as a place or position in a social group, against other groups in a larger group. Humans were created by Allah swt. as social beings who always interact with other humans. Muslims are the majority of Indonesia's population, most Muslims certainly want to visit the holy land to carry out the pilgrimage and umrah in order to perfect the fifth pillar of Islam. Performing Umrah requires a lot of money, and not all Muslims can do it. Nowadays, Umrah is easier to do by utilizing the services and services of an Umrah travel agency, one of which is by using the Umrah bailout system. Based on this, it encourages the author to raise "Review of Islamic Law on Umrah Fund bailouts for Ujas Tour & Travel" as the title of this research. Keywords: Islamic law, bailout, Umrah